(untitled) (LEARNing Landscapes, 2017)
Fitspiration has been positioned as an online interchange featuring images and text designed to inspire fitness and healthy eating. Given its ubiquity as an emerging social media trend, and its unintended impact on body image disturbance mediated by social comparison, Fitspiration has been understudied. This review draws on theoretical perspectives associated with traditional and new media impact on young women’s body image concerns, and overviews strategies to engage students in adopting a healthier body image. The manuscript also provides educational implications and directions for practice, particularly guided by media literacy models that may serve to intervene with body comparisons, inspire deeper learning and a renewed vision of fitness, health, and well-being.